P2Y12 shRNA treatment decreases SGC activation to relieve diabetic neuropathic pain in type 2 diabetes mellitus rats. Issue 12 (26th June 2018) - Wang, Shouyu; Wang, Zilin; Li, Lin; Zou, Lifang; Gong, Yingxin; Jia, Tianyu; Zhao, Shanhong; Yuan, Huilong; Shi, Liran; Liu, Shuangmei; Wu, Bing; Yi, Zhihua; et al.
Abstract : Diabetic neuropathic pain is a common complication of type 2 diabetes mellitus (DM). Activation of satellite glial cells (SGCs) in the dorsal root ganglia (DRG) plays a crucial role in neuropathic pain through the release of proinflammatory cytokines. The P2Y12 receptor is expressed in SGCs of the DRG. In this study, our aim was to investigate the role of the P2Y12 receptor on the pathological changes in diabetic neuropathic pain. The present study showed that diabetic neuropathic pain increased mechanical and thermal hyperalgesia in type 2 DM model rats. The results showed that the expression levels of P2Y12 messenger RNA (mRNA) and protein in DRG SGCs were increased in DM model rats compared with control rats. Glial fibrillary acidic protein (GFAP) and interleukin‐1β (IL‐1β) expression levels in the DRG were increased in DM rats. Upregulation of GFAP is a marker of SGC activation. Targeting the P2Y12 receptor by short hairpin RNA (shRNA) decreased the upregulated expression of P2Y12 mRNA and protein, coexpression of P2Y12 and GFAP, the expression of GFAP, IL‐1β, and tumor necrosis factor‐receptor 1 in the DRG of DM rats, and relieved mechanical and thermal hyperalgesia in DM rats. After treatment with the P2Y12 receptor shRNA, the enhancing integrated OPTICAL density (IOD) ratios of p‐P38 MAPK to P38 mitogen activated protein kinase (MAPK) in the DM rats treated with P2Y12 shRNA were significantly lower than that in the untreated DM rats. Therefore, P2Y12 shRNA treatment decreased SGC activation to relieve mechanical and thermal hyperalgesia in DM rats. Abstract : Upregulated P2Y12 in satellite glial cells (SGCs) of dorsal root ganglia (DRG) was involved in diabetic neuropathic pain. Targeting the P2Y12 receptor by short hairpin RNA decreased the upregulated expression of the P2Y12 receptor in DRG SGCs and relieved mechanical and thermal hyperalgesia in type 2 DM rats.